PELABELAN TOTAL TITIK AJAIB PADA GRAF PETERSEN - Chusnul Noeriansyah Poetri (MEJ (Mathematics Education Journal), 2017)
Suppose a graph G with vertex set V(G) and the edge set E(G) where each vertex V(G) and edge E(G) is given a one - one function and on the mapping functions using positive integers {1,2, … ,